Fuel distribution controller for ARFF trainer with BACAK BAE: enhancing practical learning in aircraft firefighting operations - Anton Abdullah; Yeti Komalasari; I Gusti Ayu Mas Oka; Muhammad Kristiawan; Direstu Amalia (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
ARFF services are vital for aviation safety, but traditional trainers struggle with fuel efficiency and environmental regulations. This study aims to develop a Fuel Distribution Controller for ARFF trainers to enhance fuel efficiency and compliance. The goal is to improve training while reducing operational costs. Borg and Gall's Research and Development (R&D) model is the foundational framework in this study. This R&D model typically comprises ten essential steps, but for this research, these steps are streamlined into three central stages: preliminary study, research development, and Validation. These stages collectively guide a methodical and structured research process, commencing with comprehensive preliminary investigations, progressing to developing a research solution, and concluding with a validation phase to ascertain the innovation's effectiveness. Professional insights from Politeknik Penerbangan Palembang inform the development of the Fuel Distribution Controller for the ARFF Trainer, aiming to improve practical aircraft firefighting training. This innovation enhances fuel efficiency, reduces environmental impact, and minimizes operational costs. The revamped system simplifies operations and provides a cost-effective, user-friendly learning experience. This achievement, verified by experts and users, holds significant promise for aircraft firefighting training and education